DAYA DUKUNG AIR DAN DISTRIBUSINYA DI KABUPATEN GORONTALO, PROVINSI GORONTALO - Matalapu, Irawan (Jurnal ENMAP (Environment and Mapping), 2025)
Water is a natural resource that is very important for life, both for domestic needs, agriculture, industry, and natural ecosystems. Along with the increasing population and economic activities, the need for water is increasing. This study aims to evaluate the status of domestic water carrying capacity and its distribution in Gorontalo Regency. Determination of water carrying capacity is done by comparing water availability and water demand. Water carrying capacity is calculated according to the method stipulated in Permen LH No. 17 of 2009 combined with spatial distribution using the Guidelines for Determining Regional DDDTLH by KLHK in 2019. The results showed that the existing water availability in Gorontalo district reached 1,376,746,875 m3/year and the water demand reached 669,190,400 m3/year. based on the criteria of Permen LH No. 17 of 2009, the status of water carrying capacity in Gorontalo district is declared surplus. The projection of water carrying capacity for the next 10 years Gorontalo Regency will remain in surplus condition. The spatial distribution of the existing water carrying capacity in Gorontalo Regency shows that there are areas that have a deficit carrying capacity status. However, this condition does not affect the overall status of water carrying capacity as long as water resources management is carried out properly.